Pengaruh Media Pembelajaran Berbasis Animasi terhadap Minat Belajar Peserta Didik Kelas VII SMP Islam Alimuddin Kabupaten Probolinggo - Eliya Hakiki Nur Sugini; Abdul Basit (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2020)
This research aims to find out the effect of the use of animation based learning media on the learning interest of students in grade VII Alimuddin Islamic High School in Probolinggo regency. The use of animation based learning media is expected to help the learning process and improve student learning outcomes.This study used the research method namely quantitative research with correlation analysis. While the sample taking technique used Sampling where the sample used was grade VII Alimuddin Islamic High School non Probability Sampling, which amounted to 45 students. The research instrument in this research damaged the likert scale with Aangket inserts 10 questions with 4 questions. Data collection techniques use archivist based observation and angkets. Research obtained in this study indicates that this calculation t is uncountable -35.206 and t table calculation (-)1,68. So calculate (-35.206) > t table 1.68 or significant 0,000 < from 0,05 So there is the animated learning media influence over class learners interest in grade VII Alimuddin Islamic High School. Meaningless H0 : rejected and Ha : received. Which means that there,s an animated learning media influence over class learners interest in grade VII Alimuddin Islamic High School Probolinggo Regency.